Lithium lanthanum zirconium composite oxide solid electrolyte doped on grain boundary and surface, its manufacturing method and use
Patent Information
- Application Number
- JP2024542100
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-14
- Filing Date
- 2023-02-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-02-13
AI Technical Summary
【0024】 以上説明したように、本発明は、粒界及び表面にドーピングしたリチウムランタンジルコニウム複合酸化物固体電解質、その製造方法及び用途を提供し、段階的にドーピングする方法により一部のドーピング元素をリチウムランタンジルコニウム複合酸化物固体電解質の粒界及び表面に位置させ、粒界におけるドーピング元素の分布状態を改善し、粒界の数を減少させ、リチウムランタンジルコニウム複合酸化物の粒界抵抗を低減させ、リチウムランタンジルコニウム複合酸化物固体電解質のイオン導電率を向上させる。ボールミル法の元素ドーピングに比べ、粒界及び表面にドーピングすることはリチウムランタンジルコニウム複合酸化物の構造、形態、結晶粒及び粒子を破壊せず、分相及び表面欠陥も発生せず、且つドーピングした元素の分布がより均一であり、ボールミル法のドーピング元素は粒子粒界内に入りにくい。本発明の技術的解決手段にて提供される粒界及び表面にドーピングした方法は汎用性を有し、リチウムランタンジルコニウム複合酸化物の粒界抵抗を高効率且つ低コストで低減することを実現し、それによりイオンの導電率を向上させ、異なる固体電解質のドーピング元素に対する需要を満たすことができる。
Smart Images

Figure 2025505105000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is filed based on a Chinese patent application bearing application number 202210149801.9 and filing date February 14, 2022, and claims priority to the Chinese patent application, the entirety of which is incorporated herein by reference.
[0002] The present invention relates to the technical field of lithium ion batteries, in particular to a grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte, its preparation method and application, which can be used in the fields of all-solid lithium metal or lithium ion batteries, semi-solid lithium ion batteries, lithium air batteries and the like. [Background technology]
[0003] Lithium-ion batteries are currently the most promising energy storage devices due to their advantages such as high operating voltage, high energy density, relatively long cycle stability and low self-discharge rate. However, the energy density of commercial lithium-ion batteries (liquid electrolyte) has already reached 260 Wh kg in 2019. -1 The current limit has been reached and will soon be reached, and the problem that liquid electrolytes are always organic solvents, there is a risk of leakage, and security accidents such as fires are likely to occur in some extreme environments, posing a major security risk is becoming more and more apparent. Therefore, using a solid electrolyte with excellent safety instead of a liquid electrolyte is an effective way to solve the above problems. An ideal solid electrolyte should have high ionic conductivity, stable interfacial compatibility, and good mechanical performance.
[0004] Lithium lanthanum zirconium oxide has become a typical representative of solid electrolytes after its first successful production in 2007, but its ionic conductivity is still two orders of magnitude lower than that of liquid electrolytes. Research has revealed that element doping is an effective way to increase the ionic conductivity of lithium lanthanum zirconium oxide. Currently, methods such as solid-state reaction method, sol-gel method, and chemical precipitation are all used to produce lithium lanthanum zirconium oxide materials. In particular, the solid-state method is the preferred method due to its advantages such as simple manufacturing process and mass production. As is well known, lithium lanthanum zirconium oxide has a polycrystalline structure, so the influence of grain boundaries on its ionic conductivity cannot be ignored. Existing research results have revealed that in lithium lanthanum zirconium oxide, grain boundary resistance has a negative effect on its ionic conductivity (Seungho Yu, Donald J. Siegel. Chem. Mater. 2017, 29, 9639-9647). Therefore, in order to increase the ionic conductivity of lithium-lanthanum zirconium composite oxide, it is important to reduce the grain boundary resistance. David et al. hot-pressed lithium-lanthanum zirconium composite oxide at 1100°C, thereby obtaining a lithium-lanthanum zirconium composite oxide sample with a higher density (99% of the theoretical density) and a larger grain size, thereby reducing the contribution of the grain boundary resistance to the total resistance (David, IN; Thompson, T.; Wolfenstine, J.; Allen, JL; Sakamoto, JJAm. Ceram. Soc. 2015, 98, 1209-1214). However, high-temperature hot pressing not only requires dedicated equipment, but also has low efficiency and is not suitable for large-scale production. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above-mentioned situation of the prior art, the present invention aims to provide a grain boundary and surface doped lithium-lanthanum zirconium composite oxide solid electrolyte, which can locate a doping element at the grain boundaries and surface of the lithium-lanthanum zirconium composite oxide solid electrolyte by grain boundary doping, thereby reducing the grain boundary resistance of the lithium-lanthanum zirconium composite oxide, and which has the advantages of high ion conductivity and low cost, as well as a manufacturing method and use thereof. [Means for solving the problem]
[0006] In order to achieve the above object, a first aspect of the present invention provides a lithium-lanthanum zirconium composite oxide solid electrolyte doped with grain boundaries and surfaces, the chemical formula of the lithium-lanthanum zirconium composite oxide solid electrolyte being Li 7-x La 3-y Zr 2-z M α O 12-β D δ where M comprises one or more cationic doping elements, D comprises one or more anionic doping elements, and 0≦x≦3, 0≦y≦1.5, 0≦z≦1, 0<α<3, 0≦β≦1.5, 0≦δ≦1.
[0007] Furthermore, the solid electrolyte contains, at its grain boundaries and on its surface, one or more of oxides of Li and M, or oxides of Li and M with Li, M and D, fluorides, sulfides, nitrogen-containing compounds, phosphates, and composites thereof.
[0008] Furthermore, the doping element M comprises one or a combination of more than one of the cations Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, B, Al, Ga, In, Si, Ge, Sn, Sb, Bi, Se, Te, Nb, Mo, Hf, Ta, W and rare earth elements other than La; Preferably, the doping element M comprises one or a combination of one or more of the cations Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In, Ge, Sn, Sb, Te, Nb, Mo, Ta, Ce, Pr, Nd, Sm, Eu, Gd, Yb, Sc, Y, More preferably, the doping element M comprises one or a combination of more than one of the cations Mn, Fe, Co, Ni, Al, Ga, Nb, Ta, Ce, Pr, Nd, Sm, Gd, Yb, Y, The doping element D comprises one or a combination of more than one of the anions N, F, P, S.
[0009] Furthermore, the molar content of the doping element M, in moles, is less than or equal to 12% of the molar amount of the solid electrolyte; The molar content of the doping element D is less than or equal to 5% of the molar amount of the solid electrolyte.
[0010] Furthermore, Li and M, or Li, M and D, exist in the grain boundaries and on the surface of the solid electrolyte in the form of one or more of oxides, fluorides, sulfides, nitrogen-containing compounds, phosphates, and composites thereof.
[0011] Furthermore, the lithium lanthanum zirconium composite oxide includes a garnet type structure.
[0012] A second aspect of the present invention provides a method for producing the lithium-lanthanum-zirconium composite oxide solid electrolyte doped at the grain boundaries and on the surface according to the first aspect of the present invention, Step S1: mixing aqueous solutions of lanthanum and zirconium compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; and suction filtering, washing, drying, and roasting the obtained precipitate to obtain lanthanum zirconium oxide; and step S2 of mixing the lanthanum zirconium oxide with liquid salts of doping elements M and Li in one or more steps under stirring conditions, drying, heat treating once or twice, and further firing once or twice to obtain a lithium-lanthanum zirconium composite oxide solid electrolyte doped at the grain boundaries and on the surface.
[0013] A third aspect of the present invention provides a method for producing the lithium-lanthanum-zirconium composite oxide solid electrolyte doped on the grain boundaries and the surface according to the first aspect of the present invention, Step S1: mixing aqueous solutions of lanthanum, zirconium and M or a part of M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; and suction filtering, washing, drying and roasting the obtained precipitate to obtain lanthanum zirconium oxide containing M; and step S2 of mixing the lanthanum zirconium oxide containing M with a liquid salt of Li or a mixed liquid salt of the remaining doping element M and Li in one or more steps under stirring conditions, drying, subjecting the mixture to one or two heat treatments, and further subjecting the mixture to one or two firings to obtain a lithium lanthanum zirconium composite oxide solid electrolyte doped at the grain boundaries and on the surface.
[0014] Furthermore, all or a part of Li is added in the form of a solid salt to the lanthanum zirconium oxide containing M.
[0015] Furthermore, the zirconium source in the mixed solution described in step S1 includes one or a combination of one or more of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate, and the lanthanum source includes one or a combination of one or more of lanthanum chloride, lanthanum nitrate, lanthanum sulfate, lanthanum acetate, and lanthanum citrate.
[0016] Furthermore, the basic substance includes at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, or hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and preferably includes at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate.
[0017] Furthermore, in step S1, the mixed solution and the basic substance are added to a reactor to carry out a precipitation reaction, the pH value during the precipitation process is controlled within the range of 4.5 to 14, preferably 5 to 10, the pH value at the end of the precipitation is controlled to 8 to 13, preferably 9 to 11, and the temperature is controlled to 0 to 120°C, preferably 10 to 80°C.
[0018] Furthermore, the liquid salt of the doping elements M and Li includes one or more combinations of nitrates, acetates, sulfates, citrates, and amino acid salt molten salts or aqueous solutions. The molar ratio of Li and M at the grain boundaries and surface is 10% to 70%. The morphology and ratio of Li and M at the grain boundaries and surface are adjusted and controlled by controlling the precipitation parameters, heat treatment of the product, and sintering temperature, time, atmosphere, etc.
[0019] Furthermore, the doping element D is added in one or more steps in the steps S1 and S2, and the doping element D is derived from one or a combination of one or more of nitrates, fluorides, phosphates, sulfates, or sulfides. The molar ratio of D in the grain boundaries and on the surface is 10% to 70%. The morphology and ratio of Li and M in the grain boundaries and on the surface are adjusted and controlled by controlling the precipitation parameters, the heat treatment of the product, and the sintering temperature, time, atmosphere, etc.
[0020] Furthermore, the roasting temperature in step S1 is 600 to 1000° C., preferably 700 to 900° C., and the roasting time is 1 to 24 hours, preferably 3 to 15 hours.
[0021] Furthermore, the heat treatment temperature in step S2 is 200 to 750° C., and preferably 400 to 600° C., the heat treatment time is 1 to 24 hours, and preferably 3 to 15 hours, the drying temperature is 50 to 200° C., and the drying time is 1 to 24 hours.
[0022] Furthermore, the firing temperature in step S2 is 700 to 1100° C., preferably 800 to 950° C., and the firing time is 1 to 24 hours, preferably 3 to 15 hours.
[0023] A fourth aspect of the present invention provides the use of the grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte according to the first aspect of the present invention in an all-solid-state lithium metal or lithium ion battery, a semi-solid lithium ion battery, or a lithium air battery. Effect of the Invention
[0024] As described above, the present invention provides a grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte, its manufacturing method and use, and by using a stepwise doping method, some doping elements are located on the grain boundaries and surfaces of the lithium lanthanum zirconium composite oxide solid electrolyte, improving the distribution state of the doping elements on the grain boundaries, reducing the number of grain boundaries, reducing the grain boundary resistance of the lithium lanthanum zirconium composite oxide, and improving the ionic conductivity of the lithium lanthanum zirconium composite oxide solid electrolyte. Compared with element doping by ball milling method, doping on grain boundaries and surfaces does not destroy the structure, morphology, crystal grains and particles of the lithium lanthanum zirconium composite oxide, does not cause phase separation and surface defects, and the distribution of the doped elements is more uniform, and the doping elements by ball milling method are less likely to enter the grain boundaries. The grain boundary and surface doping method provided by the technical solution of the present invention is versatile, and can realize the reduction of the grain boundary resistance of the lithium lanthanum zirconium composite oxide with high efficiency and low cost, thereby improving the ionic conductivity and meeting the demand for doping elements of different solid electrolytes. [Brief description of the drawings]
[0025] [Figure 1] 1 is a flowchart of a method for producing a grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the drawings in conjunction with specific embodiments. It should be understood that these descriptions are illustrative and do not limit the scope of the present invention. In addition, in the following description, descriptions of well-known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.
[0027] The first aspect of the present invention provides a lithium lanthanum zirconium composite oxide solid electrolyte doped on the grain boundary and the surface, the chemical formula of the lithium lanthanum zirconium composite oxide solid electrolyte being Li 7-x La 3-y Zr 2-z M α O 12-β D δ where M comprises one or more cationic doping elements, D comprises one or more anionic doping elements, and 0≦x≦3, 0≦y≦1.5, 0≦z≦1, 0<α<3, 0≦β≦1.5, 0≦δ≦1. Here, the grain boundaries and surface of the solid electrolyte contain one or more of oxides of Li and M, or fluorides, sulfides, nitrogen-containing compounds, phosphates, and composites thereof formed by oxides of Li and M with Li, M, and D, which effectively reduces the grain boundary resistance of the lithium lanthanum zirconium composite oxide, and thereby effectively improves its ionic conductivity.
[0028] The doping element M may comprise one or a combination of more than one of the cations Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, B, Al, Ga, In, Si, Ge, Sn, Sb, Bi, Se, Te, Nb, Mo, Hf, Ta, W and rare earth elements other than La, preferably the doping element M comprises one or a combination of more than one of Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In, Ge, Sn, Sb, Te, Nb, Mo, Ta, Ce, Pr, Nd, Sm, Eu, Gd, Yb, Sc and Y, more preferably the doping element M comprises one or a combination of more than one of Mn, Fe, Co, Ni, Al, Ga, Nb, Ta, Ce, Pr, Nd, Sm, Gd, Yb and Y, The doping element D may comprise one or a combination of more than one of the anions N, F, P, S.
[0029] In moles, the molar content of doping element M is less than or equal to 12% of the molar amount of the solid electrolyte, and the molar content of doping element D is less than or equal to 5% of the molar amount of the solid electrolyte.
[0030] Furthermore, Li and M, or Li, M and D, exist in the grain boundaries and on the surface of the solid electrolyte in the form of one or more of oxides, fluorides, sulfides, nitrogen-containing compounds, phosphates, and composites thereof.
[0031] Furthermore, the lithium lanthanum zirconium composite oxide includes a garnet type structure.
[0032] The second aspect of the present invention provides a method for preparing the grain boundary and surface doped lithium-lanthanum-zirconium composite oxide solid electrolyte according to the first aspect of the present invention, the flow chart of which is shown in FIG. 1, and the method includes a co-precipitation method and a grain boundary doping method, Step S1 of mixing aqueous solutions of lanthanum and zirconium compounds in a stoichiometric ratio required for the product to obtain a mixed solution, adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction, and suction filtering, washing, drying, and roasting the obtained precipitate to obtain lanthanum zirconium oxide, in which step S1 includes removing impurity ions in the precipitate by washing; and step S2 of mixing the lanthanum zirconium oxide with liquid salts of doping elements M and Li in one or more steps under stirring conditions, drying, heat treating once or twice, and further firing once or twice to obtain a lithium-lanthanum zirconium composite oxide solid electrolyte doped at the grain boundaries and on the surface.
[0033] A third aspect of the present invention provides a method for producing the lithium-lanthanum-zirconium composite oxide solid electrolyte doped on the grain boundaries and the surface according to the first aspect of the present invention, Step S1: mixing aqueous solutions of lanthanum, zirconium and M or a part of M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; and suction filtering, washing, drying and roasting the obtained precipitate to obtain lanthanum zirconium oxide containing M; A step S2 can be adopted in which the lanthanum zirconium oxide containing M is mixed with a liquid salt of Li or a mixed liquid salt of the remaining doping element M and Li in one or more steps under stirring conditions, and after drying, is subjected to one or two heat treatments, and further is subjected to one or two firings to obtain a lithium-lanthanum zirconium composite oxide solid electrolyte doped at the grain boundaries and the surface.
[0034] In the production methods provided in the second and third aspects, all or a part of Li may be added in the form of a solid salt to the lanthanum zirconium oxide containing M.
[0035] In the above preparation method, step S1 mainly relates to a co-precipitation method, and step S2 mainly relates to a grain boundary doping method. A lithium-lanthanum zirconium composite oxide solid electrolyte is prepared by the co-precipitation method and the grain boundary doping method, and the doping elements are located on the grain boundaries and surfaces of the lithium-lanthanum zirconium composite oxide solid electrolyte, thereby improving the distribution state of the doping elements on the grain boundaries, reducing the number of grain boundaries, reducing the grain boundary resistance of the lithium-lanthanum zirconium composite oxide, and improving the ionic conductivity of the lithium-lanthanum zirconium composite oxide solid electrolyte. This method is versatile and can meet the demands for doping elements of different solid electrolytes.
[0036] Here, the zirconium source in the mixed solution described in step S1 includes one or a combination of one or more of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate, the lanthanum source includes one or a combination of one or more of lanthanum chloride, lanthanum nitrate, lanthanum sulfate, lanthanum acetate, and lanthanum citrate, and the basic substance includes at least one of magnesium bicarbonate, urea, and hydroxide, carbonate, or bicarbonate of at least one element of ammonium, sodium, and potassium, and preferably includes at least one of sodium hydroxide, urea, ammonia water, and ammonium bicarbonate.
[0037] In step S1, the mixed solution and the basic substance are added to a reactor to carry out a precipitation reaction. The pH value during the precipitation process is controlled within the range of 4.5 to 14, preferably 5 to 10, and the pH value at the end of the precipitation is controlled within the range of 8 to 13, preferably 9 to 11. The temperature is controlled within the range of 0 to 120°C, preferably 10 to 80°C.
[0038] The liquid salts of the doping element M, Li, include one or a combination of one or more of the following nitrates, acetates, sulfates, citrates and amino acid salts molten salts or aqueous solutions.
[0039] The doping element D may be added in one or more steps in steps S1 and S2, and the doping element D comprises one or a combination of one or more of nitrates, fluorides, phosphates, sulfates or sulfides.
[0040] The roasting temperature in step S1 is 600 to 1000° C., preferably 700 to 900° C., and the roasting time is 1 to 24 hours, preferably 3 to 15 hours.
[0041] The heat treatment temperature in step S2 may be 200 to 750 ° C, preferably 400 to 600 ° C, the heat treatment time is 1 to 24 h, preferably 3 to 15 h, the drying temperature is 50 to 200 ° C, the drying time is 1 to 24 h, and the calcination temperature is 700 to 1100 ° C, preferably 800 to 950 ° C. The calcination time is 1 to 24 h, preferably 3 to 15 h. The precipitation parameters, the heat treatment of the product and the calcination temperature, time, atmosphere, etc. are controlled to adjust and control the morphology and proportion of Li and M in the grain boundary and surface. In order to meet the special requirements for the electrolyte performance of different applications, it is necessary to adjust or change the type of doping element and the microstructural structure of the electrolyte, and therefore it is necessary to adopt different heat treatment regimes, for example, heat treatment is performed in stages to allow the doping element to enter the grain boundary and surface more uniformly and stably, and treatments such as water washing and water quenching may be performed between the two stages of heat treatment. The lithium-lanthanum-zirconium composite oxide obtained as above may be sintered twice to effectively control its particle size and dispersibility. After sintering once, ball milling and surface treatment can be performed to avoid sintering and agglomeration twice.
[0042] The fourth aspect of the present invention provides the use of the grain boundary and surface doped lithium-lanthanum zirconium composite oxide solid electrolyte according to the first aspect of the present invention in all-solid-state lithium metal or lithium ion batteries, semi-solid lithium ion batteries, and lithium-air batteries. The lithium-lanthanum zirconium composite oxide solid electrolyte according to the embodiment of the present invention can be used in fields such as solid lithium metal or lithium ion batteries, semi-solid lithium ion batteries, and lithium-air batteries, to achieve higher energy density and better safety performance.
[0043] The lithium-lanthanum-zirconium composite oxide solid electrolyte powder doped on the grain boundaries and surfaces can be made into ceramics by methods such as curtain coating and hot-dip coating, and can also be mixed with a polymer or designed to produce a layered composite solid electrolyte that is more compatible with electrode materials.
[0044] The present invention will now be further described with reference to specific examples.
[0045] Comparative Example 1 The stoichiometric ratio of La(NO3)3, ZrO(NO3)2, and Mn(NO3)2 was mixed in water to prepare a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution were added to the reactor at a constant speed. The pH value during the precipitation process was controlled to 7±0.2, the final pH value was 11, and the temperature was controlled to 50°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed, and dried. The dried product was roasted at 800°C for 9 hours to obtain lanthanum zirconium manganese oxide. Li2CO3 was uniformly mixed with lanthanum zirconium manganese oxide by a ball mill and fired at 900°C for 9 hours to obtain lithium lanthanum zirconium composite oxide solid electrolyte Li7La3ZrO2 doped with Mn in the bulk phase. 1.8 Mn 0.2 O 12 The ionic conductivity was measured and found to be 1.89 × 10 -4 S / cm (25°C).
[0046] Comparative Example 2 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed in water to prepare a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution were added to the reactor at a constant speed. The pH value during the precipitation process was controlled to 7±0.2, the final pH value was 11, and the temperature was controlled to 50°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. MnO2 and Li2CO3 were mixed uniformly with lanthanum zirconium oxide by ball milling, and the mixture was fired at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3ZrO2 doped with Mn in the bulk phase. 1.8 Mn 0.2 O 12 The ionic conductivity was measured and found to be 1.56×10 -4 S / cm (25°C).
[0047] Example 1 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M in water. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 7±0.2, the final pH value is 11, and the temperature is controlled to 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Mn(NO3)2 and LiNO3 liquid salt doped with Mn and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 450°C for 10 hours, and further fired at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr doped with Mn and Li oxide on the grain boundary and surface. 1.8 Mn 0.2 O 12 The ionic conductivity was measured and found to be 6.03×10 -4 S / cm (25°C).
[0048] Example 2 La2(SO4)3 and Zr(SO4)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 0.5M. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 9±0.2, the final pH value is 10, and the temperature is controlled to 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 850°C for 8.5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Al(NO3)3 and LiNO3 liquid salts doped with Al and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 450°C for 12 hours, and further fired at 850°C for 10 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Al oxide and sulfide doped on the grain boundary and surface. 6.25 La3Zr2Al 0.25 O 11.4 S 0.6 The ionic conductivity was measured and found to be 7.01×10 -4 S / cm (25°C).
[0049] Example 3 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed. The pH during the precipitation process is 5-9, and the final pH value is 11. The temperature is controlled at 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed, and dried. The dried product is roasted at 600°C for 48 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Fe(NO3)3 and LiNO3 liquid salt doped with Fe and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 200°C for 12 hours, and further fired at 860°C for 9.5 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Fe oxide doped on the grain boundary and surface. 6.7 La3Zr2Fe 0.1 O 12 The ionic conductivity was measured and found to be 4.25×10 -4 S / cm (25°C).
[0050] Example 4 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.0M. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution were added to the reactor at a constant speed. The pH value during the precipitation process was controlled to 8±0.2, the final pH value was 9.5, and the temperature was controlled to 50°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with Co(NO3)2 and LiNO3 liquid salt doped with Co and Li in a stoichiometric ratio, dried at 80°C for 18 hours, heat-treated at 550°C for 8 hours, further calcined at 800°C for 8 hours, and finally calcined at 950°C for 7 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr doped with Li and Co oxide on the grain boundary and surface. 1.5 Co 0.5 O 12 The ionic conductivity was measured and found to be 6.86×10 -4 S / cm (25°C).
[0051] Example 5 La(NO3)3 and ZrO(NO3)2 are mixed in a stoichiometric ratio into a mixed solution with a total cation concentration of 1.0M. Under stirring conditions, the mixed solution and 4.0M ammonia aqueous solution are added to the reactor at a constant speed. The pH during the precipitation process is 9-12, and the pH value at the end of the precipitation is 9. The temperature is controlled at 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 900°C for 8 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ni and Li doped Ni(CH3COO)2 and CH3COLi liquid salt, dried at 100°C for 12 hours, heat treated at 680°C for 6.5 hours, and further fired at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr with Li and Ni oxide doped on the grain boundary and surface. 1.8 Ni 0.4 O 12 The ionic conductivity was measured and found to be 5.36×10 -4 S / cm (25°C).
[0052] Example 6 La(CH3COO)3 and Zr(CH3COO)4 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 0.5M. Under stirring conditions, the mixed solution and 3.5M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 8±0.2, the final pH value is 11, and the temperature is controlled to 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed, and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ga(NO3)3 and LiNO3 liquid salts doped with Ga and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 600°C for 6 hours, and further fired at 920°C for 8.5 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Ga oxide doped on the grain boundary and surface. 6.4 La3Zr2Ga 0.2 O 12 The ionic conductivity was measured and found to be 1.14×10 -3 S / cm (25°C).
[0053] Example 7 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M sodium hydroxide solution are added to the reactor at a constant speed. The pH during the precipitation process is 10-14, and the final pH value is 10. The temperature is controlled at 60°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 750°C for 10 hours to obtain lanthanum zirconium oxide. Lanthanum zirconium oxide is mixed stepwise with NbO(NO3)3, LiNO3 and NH4F liquid salt doped with Nb and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 600°C for 6 hours, and further fired at 940°C for 8 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li, which is doped with Li, Nb oxide and fluoride on the grain boundary and surface. 6.3 La3Zr 1.4 Nb 0.7 O 11.75 F 0.5 The ionic conductivity was measured and found to be 9.65×10 -4S / cm (25°C).
[0054] Example 8 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M sodium hydroxide solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 8±0.2, the final pH value is 9.5, and the temperature is controlled to 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 1 hour to obtain lanthanum zirconium oxide. Lanthanum zirconium oxide is mixed stepwise with Ce(NO3)3, LiNO3 and (NH4)3PO4 liquid salts doped with Ce and Li in a stoichiometric ratio, dried at 100°C for 5 hours, heat-treated at 750°C for 1 hour, and further fired at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Ce oxide and phosphate doped on the grain boundary and surface. 6.8 La 2.8 Zr2Ce 0.2 O 10.5 The ionic conductivity of the resulting solution was 5.08×10 -4 S / cm (25°C).
[0055] Example 9 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.05M sodium hydroxide solution were added to the reactor at a constant speed. The pH value during the precipitation process was controlled to 8±0.2, and the final pH value was 13. The temperature was controlled to 0°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 750°C for 10 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with Pr(NO3)3·6H2O and LiNO3 liquid salt doped with Pr and Li in the stoichiometric ratio, dried at 50°C for 24 hours, heat-treated at 200°C for 12 hours, heat-treated at 500°C for 8.5 hours, and finally calcined at 900°C for 9 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li and Pr oxide doped on the grain boundary and surface. 2.6 Zr2Pr 0.4 O12 The ionic conductivity was measured and found to be 5.56×10 -4 S / cm (25°C).
[0056] Example 10 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M sodium hydroxide solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 9±0.2. The pH value at the end of the precipitation is 10. The temperature is controlled at 80°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 850°C for 8.5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Nd(NO3)3 and LiNO3 liquid salts doped with Nd and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, then heat-treated at 530°C for 8 hours and further calcined at 900°C for 9 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li and Nd oxide doped on the grain boundary and surface. 2.2 Zr2Nd 0.8 O 12 The ionic conductivity was measured and found to be 6.59 × 10 -4 S / cm (25°C).
[0057] Example 11 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M sodium hydroxide solution were added to the reactor at a constant rate. The pH value during the precipitation process was controlled to 9±0.2, the pH value at the end of the precipitation was 10, and the temperature was controlled to 10℃ to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried, and the dried product was roasted at 650℃ for 3h, and the La(NO3)3 was dissolved in water. The lanthanum zirconium oxide was obtained, and the lanthanum zirconium oxide was mixed with Sm(NO3)3·6H2O and LiNO3 liquid salt doped with Sm and Li in a stoichiometric ratio, dried at 100°C for 6 hours, heat-treated at 500°C for 8.5 hours, sintered at 800°C for 8 hours, and then sintered at 950°C for 4 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li and Sm oxide doped on the grain boundaries and surface.2.5 Zr2Sm 0.5 O 12 The ionic conductivity was measured and found to be 5.03×10 -4 S / cm (25°C).
[0058] Example 12 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. The mixed solution and 3M sodium hydroxide solution were added to the reactor at a constant speed under stirring conditions. The pH during the precipitation process was 6-10, and the pH value at the end of the precipitation was 11. The temperature was controlled at 50°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 750°C for 10 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with Gd(NO3)3·6H2O and LiNO3 liquid salt doped with Gd and Li in the stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 460°C for 9 hours, and further calcined at 800°C for 15 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li, Gd oxide and nitrogen-containing compounds doped on the grain boundary and surface. 2.5 Zr2Gd 0.5 O 11.91 N 0.06 The ionic conductivity was measured and found to be 8.42×10 -4 S / cm (25°C).
[0059] (Example 13) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.0M, and the mixed solution and 3M urea solution were added to a reactor under stirring conditions. The reaction temperature was controlled at 120°C to carry out a precipitation reaction. The resulting precipitate was filtered, washed, and dried, and the dried product was roasted at 850°C for 8.5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with Yb(NO3)3 and LiNO3 liquid salts doped with Yb and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 500°C for 8.5 hours, and further calcined at 800°C for 15 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La2Zr2YbO with Li and Yb oxide doped on the grain boundary and surface.12 The ionic conductivity was measured and found to be 6.89 × 10 -4 S / cm (25°C).
[0060] Example 14 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 8±0.2. The pH value at the end of the precipitation is 10. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with TaO(NO3)3 and LiNO3 liquid salts doped with Ta and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, heat-treated at 550°C for 8 hours, and then fired at 700°C for 24 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Ta oxide doped on the grain boundary and surface. 6.5 La3Zr 1.5 Ta 0.5 O 12 The ionic conductivity was measured and found to be 5.48×10 -4 S / cm (25°C).
[0061] Example 15 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution and 3M ammonia aqueous solution were added to the reactor under stirring conditions. The pH value during the precipitation process was controlled to 7±0.2, and the pH value at the end of the precipitation was 9.5. The temperature was controlled at 40°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with Y(NO3)3·6H2O and LiNO3 liquid salt doped with Y and Li in the stoichiometric ratio, dried at 150°C for 8 hours, heat-treated at 530°C for 8 hours, and further calcined at 870°C for 9.5 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li and Y oxide doped on the grain boundary and surface. 1.5 Zr2Y1.5 O 12 The ionic conductivity was measured and found to be 9.12 × 10 -4 S / cm (25°C).
[0062] Example 16 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 8±0.2. The pH value at the end of the precipitation is 10. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ta(NO3)3 and LiNO3 liquid salt doped with Ta and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, heat-treated at 550°C for 8 hours, and then fired at 800°C for 15 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Ta oxide doped on the grain boundary and surface. 6.4 La3Zr 1.6 Ta 0.6 O 12 The ionic conductivity was measured and found to be 7.75×10 -4 S / cm (25°C).
[0063] (Example 17) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 10±0.2. The pH value at the end of the precipitation is 10.5. The temperature is controlled to 50°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 700°C for 15 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Cu(NO3)2 and LiNO3 liquid salt doped with Cu and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, then heat-treated at 400°C for 15 hours and further calcined at 930°C for 8.5 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr doped with Li and Cu oxide on the grain boundary and surface.1.2 Cu 1.6 O 12 The ionic conductivity was measured and found to be 6.83×10 -4 S / cm (25°C).
[0064] (Example 18) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution were added to the reactor at a constant speed. The pH value during the precipitation process was controlled to 8±0.2, the pH value at the end of the precipitation was 10, and the temperature was controlled to 40°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide was mixed with TaO(NO3)3 and LiNO3 liquid salt doped with Ta and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 550°C for 9 hours, and further calcined at 950°C for 8 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li6La3ZrTaO 12 The ionic conductivity was measured and found to be 8.35×10 -4 S / cm (25°C).
[0065] (Example 19) La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 0.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 4.5-9. The pH value at the end of the precipitation is 11. The temperature is controlled to 60°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 700°C for 15 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with TaO(NO3)3, NbO(NO3)3 and LiNO3 liquid salts doped with Ta, Nb and Li in a stoichiometric ratio. The mixture is dried at 120°C for 10 hours, then heat-treated at 580°C for 7.5 hours and further calcined at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Nb and Ta oxide doped on the grain boundary and surface. 6.6La3Zr 1.6 Ta 0.2 Nb 0.2 O 12 The ionic conductivity was measured and found to be 9.89 × 10 -4 S / cm (25°C).
[0066] (Example 20) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was used for a total cation concentration of 1.5M. 3+ and Zr 4+ The mixed solution is mixed with the above, and the mixed solution and 3M ammonia aqueous solution are added to the reactor under stirring conditions. The pH value during the precipitation process is controlled to 8±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried, and the dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with TaO(NO3)3 and LiNO3 liquid salts doped with Ta and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 550°C for 8 hours, and further fired at 1100°C for 1 hour to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Ta oxide doped on the grain boundary and surface. 6.6 La3Zr 1.8 Ta 0.85 O 12 The ionic conductivity was measured and found to be 5.09×10 -4 S / cm (25°C).
[0067] Example 21 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 0.5M. Under stirring conditions, the mixed solution and 4M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 6±0.2. The pH value at the end of the precipitation is 10. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 850°C for 5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ga(NO3)3, Al(NO3)3 and LiNO3 liquid salts doped with Ga, Al and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, heat-treated at 600°C for 6 hours, and then fired at 850°C for 10 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Al and Ga oxide doped on the grain boundary and surface. 6.1 La3Zr2Al 0.1 Ga 0.2 O 12 The ionic conductivity was measured and found to be 3.12 × 10 -3 S / cm (25°C).
[0068] Example 22 La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 6±0.2. The pH value at the end of the precipitation is 12. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 750°C for 10 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with TaO(NO3)3, LiNO3 and NH4F liquid salt doped with Ta and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 550°C for 8 hours, and further fired at 830°C for 13 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li, which is doped with Li, Ta oxide and fluoride on the grain boundary and surface. 6.5 La3Zr 1.5 Ta 0.5 O 11.75 F 0.5 The ionic conductivity was measured and found to be 8.40×10 -4S / cm (25°C).
[0069] Example 23 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution were added to the reactor at a constant rate. The pH value during the precipitation process was controlled to 5±0.2, the pH value at the end of the precipitation was 10, and the temperature was controlled to 40°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried, and the dried product was roasted at 750°C for 10h to obtain lanthanum zirconate. The lanthanum zirconium oxide was mixed with TaO(NO3)3, NbO(NO3)3, LiNO3, and NH4F liquid salt doped with Ta, Nb, and Li in a stoichiometric ratio, and then dried at 100°C for 12 hours. The mixture was then heat-treated at 500°C for 8.5 hours and then calcined at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li, in which the grain boundaries and surface were doped with Li, Ta, and Nb oxides and fluorides. 6.6 La3Zr 1.6 Ta 0.2 Nb 0.2 O 11.95 F 0.1 The ionic conductivity was measured and found to be 1.32 × 10 -3 S / cm (25°C).
[0070] (Example 24) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 8±0.2. The pH value at the end of the precipitation is 10. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with TaO(NO3)3 and LiNO3 liquid salts doped with Ta and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, heat-treated at 550°C for 9 hours, and then fired at 850°C for 11 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Ta oxide doped on the grain boundary and surface. 6.2 La3Zr1.8 Ta 0.8 O 12 The ionic conductivity was measured and found to be 8.89 × 10 -4 S / cm (25°C).
[0071] (Example 25) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution, 3M ammonium bicarbonate and ammonia water mixed solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 8±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 850°C for 8.5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Eu(NO3)2 and LiNO3 liquid salt doped with Eu and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 570°C for 7.5 hours, and further fired at 820°C for 13 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr with Li and Eu oxide doped on the grain boundary and surface. 1.1 EU 1.8 O 12 The ionic conductivity was measured and found to be 6.88×10 -4 S / cm (25°C).
[0072] (Example 26) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 9.5±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 45°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ti(NO3)4 and LiNO3 liquid salt doped with Ti and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 460°C for 9.5 hours, and further calcined at 860°C for 10.5 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr doped with Li and Ti oxide on the grain boundary and surface. 1.9 Ti 0.1 O 12 The ionic conductivity was measured and found to be 5.81×10 -4 S / cm (25°C).
[0073] Example 27 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 is mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH during the precipitation process is 5.5-11, and the pH value at the end of the precipitation is 12. The temperature is controlled at 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ca(NO3)2 and LiNO3 liquid salt doped with Ca and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 410°C for 13 hours, and further fired at 840°C for 12 hours to obtain the lithium lanthanum zirconium composite oxide solid electrolyte Li7La with Li and Ca oxide doped on the grain boundary and surface. 1.8 Zr2Ca 1.8 O 12 The ionic conductivity was measured and found to be 6.12 × 10 -4 S / cm (25°C).
[0074] (Example 28) La2(SO4)3 and Zr(SO4)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 0.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 7±0.2. The pH value at the end of the precipitation is 11. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 850°C for 8.5 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ga(NO3)3, Al(NO3)3 and LiNO3 liquid salts doped with Ga, Al and Li in a stoichiometric ratio. The mixture is dried at 100°C for 12 hours, heat-treated at 600°C for 6 hours, and then fired at 850°C for 18 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Al and Ga oxide and sulfide doped on the grain boundary and surface. 6.1 La3Zr2Al 0.1 Ga 0.2 O 11 The ionic conductivity of S was measured and found to be 4.32 × 10 -3 S / cm (25°C).
[0075] (Example 29) La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 9.5±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 45°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ga(NO3)3, LiNO3 and (NH4)3PO4 liquid salt doped with Ga and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 450°C for 12 hours, and further fired at 800°C for 15 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li4La3Zr2GaO with Li, Ga oxide and phosphate doped on the grain boundary and surface. 10.5 The ionic conductivity of the resulting solution was 9.91×10 -4 S / cm (25°C).
[0076] (Example 30) The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3M ammonia aqueous solution were added to the reactor at a constant rate. The pH value during the precipitation process was controlled to 8.5±0.2, the pH value at the end of the precipitation was 12, and the temperature was controlled to 40°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried, and the dried product was roasted at 750°C for 10h to obtain lanthanum dithiocarbamate. The lanthanum zirconium oxide was mixed with Ga(NO3)3, TaO(NO3)3, Ba(NO3)2, and LiNO3 liquid salts doped with Ga, Ba, Ta, and Li in a stoichiometric ratio, and then dried at 50°C for 24 hours. The mixture was then heat-treated at 480°C for 12 hours and then calcined at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li, with the grain boundaries and surface doped with Li, Ga, Ba, and Ta oxides. 6.4 Ga 0.1 La3Zr 1.55 Ta 0.4 Ba 0.05 O 12 The ionic conductivity was measured and found to be 8.36×10 -4 S / cm (25°C).
[0077] (Example 31) La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.05M sodium hydroxide solution are added to the reactor at a constant speed. The pH value during the precipitation process is controlled to 8±0.2. The pH value at the end of the precipitation is 12. The temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed and dried. The dried product is roasted at 750°C for 10 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Al(NO3), RbNO3 and LiNO3 liquid salts doped with Al, Rb and Li in a stoichiometric ratio. The mixture is dried at 50°C for 24 hours, heat-treated at 400°C for 15 hours, and further calcined at 900°C for 9 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li and Rb oxide doped on the grain boundary and surface. 6.1 La 2.1 Zr2Al0.3 Rb 2.7 O 12 The ionic conductivity was measured and found to be 7.96×10 -4 S / cm (25°C).
[0078] Example 32 The stoichiometric ratio of La(NO3)3 and ZrO(NO3)2 was mixed into a mixed solution with a total cation concentration of 1.5M. Under stirring conditions, the mixed solution and 3.05M sodium hydroxide solution were added to the reactor at a constant rate. The pH value during the precipitation process was controlled to 8.5±0.2, and the pH value at the end of the precipitation was 12. The temperature was controlled to 45°C to carry out the precipitation reaction. The obtained precipitate was filtered, washed and dried. The dried product was roasted at 750°C for 10h to obtain lanthanum dihydrate. The lanthanum zirconium oxide was obtained, and the lanthanum zirconium oxide was mixed with Ge(NO3)4 and LiNO3 liquid salt doped with Ge and Li in a stoichiometric ratio, dried at 50°C for 24 hours, heat treated at 400°C for 14 hours, further calcined at 700°C for 16 hours, and finally calcined at 900°C for 9 hours and then at 950°C for 8 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li7La3Zr doped with Li and Ge oxide on the grain boundaries and surface. 1.7 Ge 0.3 O 12 The ionic conductivity was measured and found to be 6.56×10 -4 S / cm (25°C).
[0079] (Example 33) La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 6.5±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 45°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed, and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Al(NO3)3, TaO(NO3)3, and LiNO3 liquid salts doped with Al, Ta, and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 600°C for 6 hours, and further fired at 850°C for 11 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Al, and Ta oxide doped on the grain boundary and surface. 6.2 Al 0.2 La3Zr 1.8 Ta 0.2 O 12 The ionic conductivity was measured and found to be 9.21×10 -4 S / cm (25°C).
[0080] (Example 34) La(NO3)3 and ZrO(NO3)2 in a stoichiometric ratio are mixed into a mixed solution with a total cation concentration of 1.0M. The mixed solution and 3M ammonia aqueous solution are added to a reactor under stirring conditions. The pH value during the precipitation process is controlled to 9.5±0.2, the pH value at the end of the precipitation is 10, and the temperature is controlled to 40°C to carry out the precipitation reaction. The obtained precipitate is filtered, washed, and dried. The dried product is roasted at 800°C for 9 hours to obtain lanthanum zirconium oxide. The lanthanum zirconium oxide is mixed with Ga(NO3)3, RbNO3, and LiNO3 liquid salts doped with Ga, Rb, and Li in a stoichiometric ratio, dried at 100°C for 12 hours, heat-treated at 550°C for 8.5 hours, and further fired at 860°C for 10.5 hours to obtain a lithium lanthanum zirconium composite oxide solid electrolyte Li with Li, Ga, and Rb oxide doped on the grain boundary and surface. 6.5 Ga 0.2 La 2.95 Rb 0.05 ZrO 12 The ionic conductivity was measured and found to be 2.01×10-3 S / cm (25°C).
[0081] As is clear from the above results, the lithium-lanthanum-zirconium composite oxide solid electrolyte obtained by employing the manufacturing method of the embodiment of the present invention has a significantly improved ionic conductivity compared to the oxide manufactured in the comparative example.
[0082] As described above, the present invention relates to a grain boundary and surface doped lithium-lanthanum zirconium composite oxide solid electrolyte, its preparation method and application, in which a part of the doping element is located on the grain boundary and surface of the lithium-lanthanum zirconium composite oxide solid electrolyte by a stepwise doping method, improving the distribution state of the doping element on the grain boundary, reducing the number of grain boundaries, reducing the grain boundary resistance of the lithium-lanthanum zirconium composite oxide, and improving the ionic conductivity of the lithium-lanthanum zirconium composite oxide solid electrolyte. The grain boundary doping method provided by the technical solution of the present invention is versatile, and can realize the efficient and low-cost reduction of the grain boundary resistance of the lithium-lanthanum zirconium composite oxide, thereby improving the ionic conductivity, and can meet the demand for doping elements of different solid electrolytes, and is suitable for large-scale application.
[0083] It should be understood that the above specific embodiments of the present invention are merely used for illustrative purposes to explain or explain the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention should be included within the protection scope of the present invention. Furthermore, the claims of the present invention are intended to include all changes and modifications within the scope and limits of the claims, or equivalent forms of such scope and limits.
Claims
1. In the solid electrolyte of the lithium lanthanum zirconium composite oxide doped on the grain boundary and the surface, the chemical formula of the solid electrolyte is Li 7-x La 3-y Zr 2-z M α O 12-β D δ wherein M comprises one or more cationic doping elements, D comprises one or more anionic doping elements, and 0≦x≦3, 0≦y≦1.5, 0≦z≦1, 0<α<3, 0≦β≦1.5, 0≦δ≦1. A grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte.
2. The lithium lanthanum zirconium composite oxide solid electrolyte doped with grain boundaries and surfaces according to claim 1, characterized in that the grain boundaries and surfaces of the solid electrolyte contain one or more of oxides of Li and M, or oxides of Li and M with Li, M and D, fluorides, sulfides, nitrogen-containing compounds, phosphates, and composites thereof.
3. The doping element M comprises one or a combination of at least one of the following cations: Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, B, Al, Ga, In, Si, Ge, Sn, Sb, Bi, Se, Te, Nb, Mo, Hf, Ta, W and rare earth elements other than La; Preferably, the doping element M comprises one or a combination of one or more of the cations Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In, Ge, Sn, Sb, Te, Nb, Mo, Ta, Ce, Pr, Nd, Sm, Eu, Gd, Yb, Sc, and Y; More preferably, the doping element M comprises one or a combination of more than one of the cations Mn, Fe, Co, Ni, Al, Ga, Nb, Ta, Ce, Pr, Nd, Sm, Gd, Yb, and Y; The grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte according to claim 1 or 2, characterized in that the doping element D comprises one or a combination of one or more of the anions N, F, P, and S.
4. The molar content of the doping element M, in moles, is less than or equal to 12% of the molar amount of the solid electrolyte (addition of Example 29), The grain boundary and surface doped lithium lanthanum zirconium composite oxide solid electrolyte according to any one of claims 1 to 3, characterized in that the molar content of the doping element D is 5% or less of the molar amount of the solid electrolyte (Example 31 is added).
5. 4. The lithium-lanthanum zirconium composite oxide solid electrolyte according to claim 1, wherein the lithium-lanthanum zirconium composite oxide has a garnet-type structure.
6. Step S1: mixing aqueous solutions of lanthanum and zirconium compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; and subjecting the resulting precipitate to suction filtration, washing, drying and roasting to obtain lanthanum zirconium oxide; and step S2 of mixing the lanthanum zirconium oxide with a liquid salt of a doping element M and Li under stirring conditions in one or more steps, drying, subjecting the mixture to one or two heat treatments, and further subjecting the mixture to one or two firings to obtain a lithium-lanthanum zirconium composite oxide solid electrolyte doped with grain boundaries and surfaces.
7. Step S1: mixing aqueous solutions of lanthanum, zirconium, and M or a part of M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; and suction filtering, washing, drying, and roasting the obtained precipitate to obtain a lanthanum zirconium oxide containing M; and step S2 of mixing the lanthanum zirconium oxide containing M with a liquid salt of Li or a mixed liquid salt of the remaining doping element M and Li in one or more steps under stirring conditions, drying, subjecting the mixture to one or two heat treatments, and further subjecting the mixture to one or two firings to obtain a lithium lanthanum zirconium composite oxide solid electrolyte doped with grain boundaries and surfaces.
8. 8. The method according to claim 6, wherein all or a part of Li is added in the form of a solid salt to the lanthanum zirconium oxide containing M.
9. 8. The method according to claim 6 or 7, wherein the zirconium source in the mixed solution described in step S1 comprises one or more combinations of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate, and the lanthanum source comprises one or more combinations of lanthanum chloride, lanthanum nitrate, lanthanum sulfate, lanthanum acetate, and lanthanum citrate.
10. 8. The method according to claim 6 or 7, characterized in that the basic substance comprises at least one of magnesium hydrogen carbonate, urea and hydroxide, carbonate or hydrogen carbonate of at least one element of ammonium, sodium and potassium, preferably at least one of sodium hydroxide, urea, aqueous ammonia and ammonium hydrogen carbonate.
11. The method according to claim 6 or 7, characterized in that in step S1, the mixed solution and the basic substance are added to a reactor to carry out a precipitation reaction, the pH value during the precipitation is controlled in the range of 4.5 to 14, preferably 5 to 10, the pH value at the end of the precipitation is controlled in the range of 8 to 13, preferably 9 to 11, and the temperature is controlled in the range of 0 to 120°C, preferably 10 to 80°C.
12. 8. The method according to claim 6 or 7, characterized in that the liquid salts of the doping elements M, Li, comprise one or a combination of one or more of the following: nitrates, acetates, sulfates, citrates and amino acid salts molten salts or aqueous solutions.
13. 8. The method according to claim 6 or 7, characterized in that a doping element D is added in one or more stages in steps S1 and S2, and the doping element D is derived from one or a combination of one or more of the following: nitrates, fluorides, phosphates, sulfates and sulfides.
14. The method according to claim 6 or 7, wherein the roasting temperature in step S1 is 600-1000°C, preferably 700-900°C, and the roasting time is 1-24h, preferably 3-15h.
15. The method according to claim 6 or 7, characterized in that the heat treatment temperature in step S2 is 200-750°C, preferably 400-600°C, and the heat treatment time is 1-24h, preferably 3-15h.
16. The method according to claim 6 or 7, characterized in that the firing temperature in step S2 is 700-1100°C, preferably 800-950°C, and the firing time is 1-24h, preferably 3-15h.
17. Use of the lithium lanthanum zirconium composite oxide solid electrolyte having grain boundaries and a surface doped therein according to any one of claims 1 to 5 in all-solid lithium metal or lithium ion batteries, semi-solid lithium ion batteries, and lithium air batteries.
Citation Information
Patent Citations
Garnet-type lithium-lanthanum-zirconium composite oxide and method for producing the same
JP2018065704A
Method for producing garnet-type inorganic materials
JP2022543028A
Process for preparing doped lithium lanthanum zirconium oxide
US20210198117A1
Method of preparation of a garnet-type inorganic material
WO2021023599A1